2018
DOI: 10.12957/demetra.2018.32295
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade De Vida De Crianças E Adolescentes Com Fibrose Cística: Importância Da Imagem Corporal E Impacto Do Estado Nutricional, Idade E Raça/Cor Na Percepção Dos Pacientes E Responsáveis

Abstract: ResumoObjetivo: Identificar os principais fatores relacionados à qualidade de vida de crianças e adolescentes com fibrose cística. Métodos: Estudo transversal, com indivíduos com fibrose cística, entre 7 e 18 anos, de um Centro de Referência Estadual. A qualidade de vida foi avaliada com o Cystic Fibrosis Questionnaire. Testes usados na análise estatística: Mann-Whitney e Correlação de Spearman. Nível de significância adotado: 5%. Resultados: Na percepção dos pacientes, os domínios da qualidade de vida com pio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
2
0
3
Order By: Relevance
“…In addition, PEF and PCF values were similar in an earlier study in CF patients [31], and PCF reduction has been reported in children and adolescents with CF [9]. This variable deserves attention because it is known that cough is an important physiological mechanism for bronchial hygiene, which is essential for the prevention of recurrent infections and bacterial colonization, which accelerate the decline of pulmonary function in CF [1,32,33], with an impact on quality of life [2,3] and mortality due to the disease [1,32,33].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In addition, PEF and PCF values were similar in an earlier study in CF patients [31], and PCF reduction has been reported in children and adolescents with CF [9]. This variable deserves attention because it is known that cough is an important physiological mechanism for bronchial hygiene, which is essential for the prevention of recurrent infections and bacterial colonization, which accelerate the decline of pulmonary function in CF [1,32,33], with an impact on quality of life [2,3] and mortality due to the disease [1,32,33].…”
Section: Discussionmentioning
confidence: 59%
“…Cystic fibrosis (CF) is an autosomal recessive genetic disease that has a high mortality rate [1] and a major impact on quality of life starting in childhood [2][3]. The genetic mutations in CF compromise ion transport across epithelial cell membranes, which causes dysfunction of the exocrine glands and consequent dehydration of secretions and obstructions.…”
Section: Introductionmentioning
confidence: 99%
“…Na cognição do responsável, o peso corporal médio também é o pior. A partir dos 14 anos, o tratamento tem maior impacto na qualidade de vida, enquanto as crianças menores de 14 anos têm maior impacto na alimentação (SILVA et al, 2018).…”
Section: Discussionunclassified
“…Os resultados mostraram alta prevalência de risco nutricional na amostra (70,6%), o que é frequente nas crianças e adolescentes com FC [3][4][5]20,32,35]. Não houve diferença significativa entre os pacientes colonizados por Pseudomonas aeruginosa e Staphylococcus aureus, em relação às variáveis nutricionais, o que corrobora um estudo longitudinal recente, realizado no Brasil, que mostrou que o estado nutricional não foi fator de risco para infecção por P. aeruginosa [36].…”
Section: Discussionunclassified
“…O mau funcionamento do pâncreas exócrino causa comprometimento nutricional devido à má absorção e esteatorréia, comuns desde o nascimento. A desnutrição contribui para o déficit de crescimento [3] e está relacionada ao declínio da função pulmonar [3,4], e da qualidade de vida [5].…”
Section: Introductionunclassified